A framework for understanding the pathophysiology of functional neurological disorder - Drane, Daniel L.; Fani, Negar; Hallett, Mark; Khalsa, Sahib S.; Perez, David L.; Roberts, Nicole A. (CNS spectrums, 2021)
The symptoms of functional neurological disorder (FND) are a product of its pathophysiology. The pathophysiology of FND is reflective of dysfunction within and across different brain circuits that, in turn, affects specific constructs. In this perspective article, we briefly review five constructs that are affected in FND: emotion processing (including salience), agency, attention, interoception, and predictive processing/inference. Examples of underlying neural circuits include salience, multimodal integration, and attention networks. The symptoms of each patient can be described as a combination of dysfunction in several of these networks and related processes. While we have gained a considerable understanding of FND, there is more work to be done, including determining how pathophysiological abnormalities arise as a consequence of etiologic biopsychosocial factors. To facilitate advances in this underserved and important area, we propose a pathophysiology-focused research agenda to engage government-sponsored funding agencies and foundations.